Developing linguistic and cultural competence: participants’ evaluation of a Maltese language and culture awareness program - SCHEMBRI, NEVILLE (Advances in Social Sciences Research Journal, 2021)
Malta is facing an increasing demand and decreasing supply of local nurses and engagement of culturally and linguistically diverse (CALD) personnel is becoming the main solution to mitigate such problems. The case study examines the perceptions of CALD nurses about the content and utility of a Maltese language and culture awareness program. A qualitative methodology was adopted and data collected through focus group interviews conducted with sixteen (16) participants. Qualitative content analysis using Framework Method was used to analyse the data. Views on the training program have been divided between elements related to individual utility, service user utility, quality of delivery and areas for improvement. The results indicate that training can provide significant advantages in terms of enhancing cultural competence and cross-cultural encounters amongst CALD nurses working in elderly long term care and it is recommended that such programs are encouraged to be taken on board by organisations operating in similar health and social care services.